2013 Malaysian election : an empirical study on strategic allocation model - Tan, Sook Rei (2014)
Numerous studies have been conducted to examine the impact of strategic decisions on the election outcome in the United States presidential election. Conversely, such empirical research and analysis in Malaysia have yet to be done. In this paper, we will be using a game theoretical approach to analyze the 2013 Malaysian Election, seeking to investigate whether parties engage in strategic allocation of resources over electorates. In this closest race ever in Malaysia’s election history, the opposition won 51% of popular votes but lost in the election with only 89 out of 222 parliamentary seats obtained. As such, the first model of this paper aims to identify the rationality attributes to such interesting outcome. The empirical results suggest that the election is a strategic allocation game, where resource distribution plays a pivotal role in affecting parties’ winning chances. The second model describes the factors affecting parties’ strategic decisions. It is observed that both coalition parties used different approaches in allocating their strategy. From our findings, we infer that the loss of opposition was largely the result of strategic mistakes. Hence, further investigation is made to identify the ex post mistakes done by the opposition. Alternative strategies which could possibly overturn the election outcome are then explored.